Prevalence of mental disorders among young males in Swedish compulsory residential care - Jalling, Camilla; Kristiansson, Marianne (Frontiers in Psychiatry, 2025)
IntroductionThis study sought to examine the prevalence of diagnosed and undiagnosed psychiatric disorders, comorbidity, and acute psychiatric conditions among young males in compulsory residential care due to criminality, substance misuse, or other socially destructive behavior pattern.MethodsAn online cross-sectional survey measured diagnosed and undiagnosed mental disorders listed in DSM-5, and other psychiatric conditions among children and youth admitted to the Swedish National Board of Institutional Care. Psychologists at the residential homes answered one questionnaire per young male participant by retrieving information from records and other relevant files. ResultsData for 183 residing young males were analyzed. The prevalence of diagnosed mental disorders was high (77%), and psychiatric comorbidity was present among 46%. ADHD was the most common diagnosis (57%), followed by SUD (20%), CD (14%), ASD (14%), and PTSD (12%). Furthermore, a large proportion of the young males had displayed clinical symptoms without being diagnosed, and 10% had been in a state of acute psychiatric distress.DiscussionSeveral findings in this study align with previous research, such as the prevalence of diagnosed conditions and co-morbidities. Some results did diverge, however, and ADHD and SUD were found to have higher prevalences in our study, while CD was considerably lower compared to previous findings. It remains unclear why CD prevalence was low, but it may have to do with the high prevalence of ADHD, and a general reluctance to assess for CD. In Sweden, where this study was carried out, both clinical and general awareness of ADHD has increased over the last two decades, alongside revised diagnostic criteria in DSM-5, which may have improved identification, and assessment, and led to an increase in diagnoses. It may also, in part, have led to clinicians prioritizing assessments of ADHD over CD.